Students’ Perception in Reading English Novel - Arfini, Fifi; Qalby, Nur; Daddi, Herlina (FKIP Unismuh Makassar, 2024)
The objective of this research is researcher conducted several indicators that in improving students' language and cultural awareness. The researcher used descriptive-quantitative research where the data gained from the questionnaires. The population of the research was the sixth semester of English Education FKIP Unismuh Makassar. The sample was taken by using purposive sampling technique there were 20 students.The result showed that mostly students perceived that reading novel can make it easier for students to understand language improvement and cultural awareness based on the values showed in table 4.11 is 5% disagree and 95% Partially agree to Strongly Agree in their daily activities. It means that, language improvement and cultural awareness of students can be increased through Reading English Novels.It was concluded that there was an improvement in students' writing skills related to content and organization writing skills in the use of tutorial video.